Effects of Cola Nut [Cola Nitida (Vent.) Schott & Endl.] Aqueous Extract on Rat Liver During Hepatocarcinogenesis - Kadivar, Mohammad (2010)
The effect of Cola nitida aqueous extract in hepatocarcinogenesis induced male Sprague Dawley rat livers, and elemental analysis of the cola nut was studied to investigate the possible anticancer activity. The unprocessed cola nuts were observed for their surface morphological structure under the scanning electron microscope (SEM). Together with the imaging, samples were then elementally analyzed using energy dispersive x-ray microanalysis attached to variable pressure scanning electron microscopy (EDX-VPSEM). SEM study of cola nut illustrates numerous crystals packed in clusters within the cell wall. The elemental analysis results revealed that the cola nut contained high amount of oxygen and carbon, in addition to potassium, phosphorus and magnesium. Potassium, magnesium and phosphorous have been well reported as co-factors of antioxidant enzymes to protect the body from oxygen free radicals. Additionally, these elements play important roles in metabolic mechanisms in the body. Hepatocarcinogenesis was induced in rat livers according to the modified Solt and Farber method. Diethylnitrosamine (DEN) was injected into the rats at 200 mg/kg body weight to initiate hepatocarcinogenesis and after two weeks this was followed by feeding 0.02% 2-Acetylaminofluorene (AAF) to promote the hepatocarcinogenesis. The DEN/AAF induced rats were treated with 1, 2.5, and 5% (w/v) concentrations of cola nut extract or 0.001, 0.0025, and 0.005% w/v dilutions of glycyrrhizin as a drug control. There were normal and cancer controls; in addition, three groups of normal rats were treated with three concentrations of cola nut to observe the side effect of the cola nut on normal livers. The body and liver weight profile results of this study showed no significant difference between treated groups compared to normal and cancer controls. The similarity in body weight gain and relative liver weight results might occur because of the short length of the in vivo experiment (eleven weeks). The supplementation of cola nut extract decreased the level of plasma and microsomal GGT and GST tumor marker enzymes significantly in DEN/AAF induced liver tissues even better than glycyrrhizin. Additionally, it was revealed that cola nut extract has no effect on the level of GST and GGT enzymes in normal cells. The histological and ultrastructural examination as well as the lesions scoring results demonstrated that the cola nut extract reduced neoplastic stage of the hepatocarcinogenic liver cells more than glycyrrhizin based on their abnormal morphology, inflammation, necrosis, and fibrosis. Moreover, rat’s normal hepatocytes treated with cola nut extract illustrated normal features. TUNEL assay results showed the significant increase in the number of apoptotic cells in hepatocarcinogenic liver tissues treated with cola nut extract and glycyrrhizin. These results showed that cola nut did not induce the apoptosis in normal liver cells. Quantitative real-time RT-PCR results revealed that although the level of alpha-fetoprotein (AFP) mRNA increased in DEN/AAF induced liver cells, but the supplementation of the cola nut and glycyrrhizin decreased it predominantly in hepatocarcinogenic liver cells treated with cola nut extract. These findings suggest that cola nut might act as a promising anticancer against hepatocarcinogenesis with even higher efficacy compared to glycyrrhizin, without any side effects in normal liver cells.